Peningkatan Pengetahuan Ibu Balita Tentang Pemberian Makan Bayi dan Anak (PMBA) Di Desa Jetis - Dwi Rosella Komalasari; Amar busro; Lu'lu'ul Muslimah; Tiara Sang Ether Asy shifa; Aviva Tunisyia; Valentina Febri Marzaleva; Rabiatul Adawiya (STIKes Ibnu Sina Ajibarang, 2024)
The practice of feeding infants and children (PMBA) by mothers of toddlers must be carried out correctly and precisely. Mistakes in feeding toddlers will result in malnutrition in children and result in stunting. Prevention of stunting needs to be balanced with the knowledge and understanding of mothers of toddlers about PMBA. This activity aimed to provide education to mothers of toddlers about the importance of feeding infants and children well (PMBA). The method used is to provide education about PMBA demonstrate making modisco and measure the level of knowledge of mothers of toddlers before and after the activity to determine changes in knowledge in mothers of toddlers. The evaluation results obtained regarding the level of knowledge of mothers of toddlers before the activity was carried out, most participants were in the poor category (88.6%), while after the activity the level of knowledge of most participants was good (95.5%)